Areal Specific Resistance: The Ab Initio Calculations on the Areal Specific Resistance of Li‐Metal/Li7La3Zr2O12 Interphase (Adv. Theory Simul. 6/2019). Issue 6 (4th June 2019) - Gao, Jian; Guo, Xuyun; Li, Yutao; Ma, Zhaohui; Guo, Xiangxin; Li, Hong; Zhu, Ye; Zhou, Weidong
Abstract : Understanding the origin of high interfacial resistance between Li/Li7La3 Zr2 O12 (LLZO) is crucial for the power density and stability. Here, ab initio calculations confirm the moderate intrinsic areal specific resistance and thermodynamic decomposition tendency of LLZO into Li2 O. The atmosphere CO2 sets up Li2 CO3 barriers to prohibit Li permeation, and H2 O increases the amount of Li2 CO3 by exchanging more Li with H. More details can be found in article number1900028 by Yutao Li, Ye Zhu, Weidong Zhou, and co‐workers.